(untitled) (Tumou Tou: Jurnal Pengabdian Masyarakat, 2025)
Kema I Village, located in Kema Sub-district, North Minahasa Regency, is predominantly an agricultural community where corn farming plays a central role. While corn production supports the local economy, it also generates large volumes of corn husk waste, which are typically burned by farmers. This practice contributes to environmental pollution and reflects the lack of effective waste management strategies. This community engagement project aimed to provide an innovative and sustainable solution by empowering local residents—particularly women’s groups to transform dried corn husks into handcrafted products with both aesthetic and economic value. The method involved direct observation, community interviews, and hands-on training sessions on crafting techniques and marketing approaches. The initiative resulted in increased awareness of environmental issues and equipped residents with alternative income-generating skills. The use of agricultural waste for productive purposes not only reduced open burning practices but also contributed to improving the quality of the settlement environment. This approach demonstrated how waste reuse and community empowerment can serve as a practical strategy for mitigating slum-like conditions in rural areas. Overall, this program highlights the importance of integrating local resources, environmental awareness, and creativity to support sustainable rural development.